2022
DOI: 10.1186/s13619-022-00107-w
|View full text |Cite
|
Sign up to set email alerts
|

Human embryos in a dish – modeling early embryonic development with pluripotent stem cells

Abstract: Stem cell-based embryo models present new opportunities to study early embryonic development. In a recent study, Kagawa et al. identified an approach to create human pluripotent stem cell-based blastoids that resemble the human blastocysts. These blastoids efficiently generated analogs of the EPI, TE, PrE lineages with transcriptomes highly similar to those found in vivo. Furthermore, the formation of these lineages followed the same sequence and pace of blastocyst development, and was also dependent on the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…4 ). These capabilities illustrate its potential as a powerful tool for studying human early embryonic developmental processes in vitro ( 16, 41 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…4 ). These capabilities illustrate its potential as a powerful tool for studying human early embryonic developmental processes in vitro ( 16, 41 ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies have reported methods called "blastoids" to generate blastocyst-like structures in mouse models (10)(11)(12). Recently, three groups reported the generation of human blastoids (13)(14)(15)(16). Liu et al (2021) used cells during the reprogramming process from fibroblasts to human pluripotent stem cells (hPSCs), as these cells contained a variety of cells, including cells with EPI-, TE-, and PE-like transcriptional signatures (13).…”
mentioning
confidence: 99%
“…Human pluripotent stem cells (hPSCs) have the capacity to differentiate into different cell types. They can be derived from the cells within the blastocyst at the beginning of embryonic development, from which the various structures of the fetus originate [159], or they can be derived from human cells that are de-differentiated by expression of Yamanaka factors (Oct3/4, Sox2, Klf4, c-Myc), known as induced pluripotent stem cells (iPSCs) [160].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%